Electroless silver plating of 3D printed waveguide components by peristaltic pump driven system. Issue 2 (1st January 2019) - Bal, A.; Carey, D.G.; Espinal, F.A.; Huff, G.H.
Abstract : V‐band waveguide components operating in 57–64 GHz ISM band is presented. Consumer‐grade stereolithographic 3D printer is used to print these waveguide components with black‐pigmented acrylate‐based polymer. Electroless deposition of silver on these microwave components is achieved using an in‐house system assembled with off‐the‐shelf components. This system is driven by a peristaltic pump, circling plating solution between silver bath and waveguide. Metal plated WR‐15, 2‐inch waveguide section offers average insertion coefficient of −0.35 dB. Trough waveguide section connected to rectangular waveguide through rectangular to trough waveguide transition is metal plated and offers average insertion coefficient of −1 dB. Silver deposited using the pump operated system offers potential of achieving comparable results as conventional dip coating technique.